L’amour du dictionnaire - Bertrand Geay (Cahiers de la Recherche sur l'Education et les Savoirs)
Representations and functions of monolingual dictionary as well as its use in daily life, are very closely related to individuals social position and school biography. An interview with three french peasants, taken from a larger field work corpus dealing with that subject, and treated as an exemplary situation, shows that an important part of learning and school culture comes into play through the use of this kind of tool. Entering the material and symbolic world of these three unlikely and all the same aware users, one can see some of the effects which structure school socialisation on the long-term basis.